Development of a Menu of Mangroves to Increase Knowledge of the Mangrove Ecotourism Group (Pokdarwis) Sekotong West Lombok - Al-Idrus, Agil; Bayani, Faizul; Ferniawan, Ferniawan; Swati, Ni Nengah Sri; Rahmawati, Sri; Liswijaya, Liswijaya; Wardani, Intan Kusuma (Jurnal Ilmiah Mandala Education (JIME), 2024)
Mangrove ecotourism in Sekotong, Lombok Barat, holds immense potential for education and local economic development. However, there are still limitations in effectively communicating mangrove education information to tourists and local communities. This study aims to determine the role of "Menu of Mangrove" in raising awareness and knowledge about the mangrove ecosystem among Pokdarwis (tourism awareness groups) and visitors, as well as transforming the traditional perspective on ecotourism visits. The research employs a qualitative approach with a case study design. Data collection methods include participant and structured observation, in-depth interviews, FGD (Focus Group Discussion), and document analysis. The data analysis techniques used are descriptive and qualitative analysis. The findings of the study demonstrate that Menu of Mangrove is an effective innovation in enhancing awareness and knowledge about the mangrove ecosystem among Pokdarwis and visitors. Menu of Mangrove also successfully transforms the traditional perspective on mangrove ecotourism visits and motivates Pokdarwis to better understand and conserve the mangrove ecosystem.Keywords: Menu of Mangrove, Mangrove Ecotourism, Mangrove Education